2003
DOI: 10.1097/00005344-200309000-00004
|View full text |Cite
|
Sign up to set email alerts
|

ERK1/2-Mediated Vasoconstriction Normalizes Wall Stress in Small Mesenteric Arteries During NOS Inhibition In Vivo

Abstract: As in essential hypertension, chronic nitric-oxide synthase (NOS) inhibition leads to hypertrophic remodeling in conduit and muscular arteries and inward eutrophic remodeling in small resistance arteries with activation of extracellular signal-regulated kinases 1 and 2 (ERK1/2) in both vessel types. The authors tested the hypothesis that this remodeling heterogeneity could be related to distinct vasoreactivity patterns in small and larger arteries, with a vessel-specific function of ERK1/2 signaling. Using int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Indeed, a single i.p. dose of PD98059 had no effect on blood pressure in rats treated with NO synthase inhibitor, although it reduced contractility of mesenteric arteries to which this inhibitor has easier and quick access via this route (Girardot et al, 2003). In separate experiments, we also observed no effect of a single PD98059 dose on blood pressure, aortic and renal ERK phosphorylation, and renal Na + ,K + -ATPase activity in leptin-treated rats.…”
Section: Discussionmentioning
confidence: 55%
“…Indeed, a single i.p. dose of PD98059 had no effect on blood pressure in rats treated with NO synthase inhibitor, although it reduced contractility of mesenteric arteries to which this inhibitor has easier and quick access via this route (Girardot et al, 2003). In separate experiments, we also observed no effect of a single PD98059 dose on blood pressure, aortic and renal ERK phosphorylation, and renal Na + ,K + -ATPase activity in leptin-treated rats.…”
Section: Discussionmentioning
confidence: 55%
“…It leaves little doubt that the initial mode of action of L -NAME is by vasoconstriction [23,24,25], amongst others related to impaired shear stress sensing. The raised resistance vessel tone increases peripheral resistance and, through central regulation, the blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…However, CSA increased only in the aorta, confirming that remodeling is heterogeneous along the vascular tree. 5 Thus, the aorta adapted to sustained pressure elevation by hypertrophic remodeling, whereas mesenteric resistance arteries underwent eutrophic remodeling. Interestingly, this heterogeneity also occurs in essential hypertension, 24,25 making the L-NAME model particularly suitable to study hypertension-induced vascular remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…2 To explain this different response between large and small arteries, it is suggested that small arteries are not submitted to an augmented wall stress because they are initially constricted. [3][4][5] Thus, we hypothesized that inward eutrophic remodeling, which appears as a fixed form of vasoconstriction, could proceed through specific modifications of VSMC-matrix interactions.…”
mentioning
confidence: 99%